2021
DOI: 10.1002/aws2.1265
|View full text |Cite
|
Sign up to set email alerts
|

Comparing centralized and point‐of‐use treatments of per‐ and polyfluoroalkyl substances

Abstract: Per‐ and polyfluoroalkyl substances (PFAS) chemicals are a growing threat to public health and safety. This study seeks to compare the life cycle environmental, economic, and human health performances of centralized and point‐of‐use (POU) systems used to upgrade existing drinking water treatment facilities for enhanced PFAS removal, using Merrimack, NH as a testbed. Out of all studied system upgrade scenarios, a POU scenario that combines granular activated carbon and ion exchange filters has the lowest enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“… Cost modeling needs to include the useful life and replacement frequency of all components of either a centralized improvement or a POU/POE device to capture the total cost over time of operating and maintaining the improvement. Other studies (Bixler et al, 2021) have examined net present value or worth using an average useful life and a functional unit based on the volume of water treated which may not accurately account for the total cost over time to a community. State and CWS‐specific cost assumptions need to be clearly documented and reported so that future studies can accurately compare results and make informed decisions. When reviewing the literature to conduct this study, we identified several different cost models and assumptions that needed careful evaluation to determine their applicability to our study.…”
Section: Considerations For Methodology Applicationmentioning
confidence: 99%
See 4 more Smart Citations
“… Cost modeling needs to include the useful life and replacement frequency of all components of either a centralized improvement or a POU/POE device to capture the total cost over time of operating and maintaining the improvement. Other studies (Bixler et al, 2021) have examined net present value or worth using an average useful life and a functional unit based on the volume of water treated which may not accurately account for the total cost over time to a community. State and CWS‐specific cost assumptions need to be clearly documented and reported so that future studies can accurately compare results and make informed decisions. When reviewing the literature to conduct this study, we identified several different cost models and assumptions that needed careful evaluation to determine their applicability to our study.…”
Section: Considerations For Methodology Applicationmentioning
confidence: 99%
“…Cost modeling needs to include the useful life and replacement frequency of all components of either a centralized improvement or a POU/POE device to capture the total cost over time of operating and maintaining the improvement. Other studies (Bixler et al, 2021) have examined net present value or worth using an average useful life and a functional unit based on the volume of water treated which may not accurately account for the total cost over time to a community. 2.…”
Section: Life Cycle Costingmentioning
confidence: 99%
See 3 more Smart Citations